The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-21622-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterogeneous network-based method for drug response prediction in cancer cell lines

Abstract: An enduring challenge in personalized medicine lies in selecting a suitable drug for each individual patient. Here we concentrate on predicting drug responses based on a cohort of genomic, chemical structure, and target information. Therefore, a recently study such as GDSC has provided an unprecedented opportunity to infer the potential relationships between cell line and drug. While existing approach rely primarily on regression, classification or multiple kernel learning to predict drug responses. Synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 52 publications
0
71
0
Order By: Relevance
“…In addition to genomic and chemical features, previous studies have demonstrated the value of complementing drug sensitivity prediction models with prior knowledge in the form of protein-protein interactions (PPI) networks (Oskooei et al, 2018b). For example, in a network-based per-drug approach integrating these data sources, Zhang et al (2018a) surpassed various earlier models and reported a performance drop of 3.6% when excluding PPI information. However, all previous attempts at incorporating chemical information in drug sensitivity prediction rely on molecular fingerprints as chemical descriptors.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to genomic and chemical features, previous studies have demonstrated the value of complementing drug sensitivity prediction models with prior knowledge in the form of protein-protein interactions (PPI) networks (Oskooei et al, 2018b). For example, in a network-based per-drug approach integrating these data sources, Zhang et al (2018a) surpassed various earlier models and reported a performance drop of 3.6% when excluding PPI information. However, all previous attempts at incorporating chemical information in drug sensitivity prediction rely on molecular fingerprints as chemical descriptors.…”
Section: Related Workmentioning
confidence: 99%
“…An example is molecular medicine, where analogue concepts are used to study gene association (e.g. van Laarhoven & Marchiori, ; Menden et al, ; Yamanishi, Araki, Gutteridge, Honda, & Kanehisa, ; Zhang, Wang, Xi, Yang, & Li, ) or harmful drug–drug interactions (e.g. Cheng & Zhao, ; Tari, Anwar, Liang, Cai, & Baral, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, network analysis in graph theory has been increasingly recognized as a useful tool for studying cancer. Such studies include the prediction of outcomes of ovarian cancer treatment (Zhang et al, 2013), analysis of breast cancer progression and reversal (Parikh et al, 2014), drug response prediction in cancer cell lines (Zhang et al, 2018), identification of novel cancer gene candidates (Josef Gladitz et al, 2018), tumor biology for precision cancer medicine (Ozturk et al, 2018), and prediction of cancer recurrence (Ruan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%